EVALUATION OF THE INFRAORBITAL COMPLEX BY DIRECT MORPHOMETRY - Maria Justina Roxana Vîrlan; Cătălina Murariu-Măgureanu; Simona Andreea Moraru; Vlad Iliescu; Ovidiu Romulus Gherghiţă; Vanda Roxana Nimigean; Ovidiu Muşat; Victor Nimigean (Romanian Society of Oral Rehabilitation, 2020)
The infraorbital complex belongs to the maxillary bone and it is an important landmark in dentistry, especially for loco-regional anaesthesia. For this study, bilateral measurements of the components of the infraorbital complex on twenty dry dentated human skulls were performed. Results: the average length of the the infraorbital groove (IOG) was 12.55 mm and the average length of the infraorbital canal (IOC) was 12.92 mm. Regarding the infraorbital foramen (IOF), its shape was oval in 65% of the cases and the average distance between the infraorbital foramen and the inferior orbital margin (IOF-IOM distance) was 7.87 mm. IOF was located on the vertical line drawn between premolars in 50% of the cases and on the vertical line drawn through the axis of the maxillary second premolar in 45% of the cases. The morphometric data obtained can be useful in dentoalveolar surgery.